Rural eHealth Nutrition Education for Limited-Income Families: An Iterative and User-Centered Design Approach - Atkinson, Nancy L; Saperstein, Sandra L; Desmond, Sharon M; Gold, Robert S; Billing, Amy S; Tian, Jing (JMIR Publications, 2009)
Background Adult women living in rural areas have high rates of obesity. Although rural populations have been deemed hard to reach, Internet-based programming is becoming a viable strategy as rural Internet access increases. However, when people are able to get online, they may not find information designed for them and their needs, especially harder to reach populations. This results in a "content gap" for many users. Objective User-centered design is a methodology that can be used to create appropriate online materials. This research was conducted to apply a user-centered approach to the design and development of a health promotion website for low-income mothers living in rural Maryland. Methods Three iterative rounds of concept testing were conducted to (1) identify the name and content needs of the site and assess concerns about registering on a health-related website; (2) determine the tone and look of the website and confirm content and functionality; and (3) determine usability and acceptability. The first two rounds involved focus group and small group discussions, and the third round involved usability testing with individual women as they used the prototype system. Results The formative research revealed that women with limited incomes were enthusiastic about a website providing nutrition and physical activity information targeted to their incomes and tailored to their personal goals and needs. Other priority content areas identified were budgeting, local resources and information, and content that could be used with their children. Women were able to use the prototype system effectively. Conclusions This research demonstrated that user-centered design strategies can help close the "content gap" for at-risk audiences.